Interna in eksterna rekonstrukcija v slovanski etimologiji - Furlan, Metka (Slavistična revija, 2008)
Alternating application of internal and external reconstruction is in Slavic etymology indispensal, because otherwise, that is without permanent addition of data from other non-Slavic Indo-European languages, Slavic etymolgy would be the etymology of much more limited possibilities of interpretations.
Keywords: etimologija; primerjalno jezikoslovje; rekonstrukcija; slovanski jeziki